Simultaneous Spectrophotometric Estimation of Aceclofenac and Paracetamol - NIKAM, A.D.; PAWAR, S.S.; GANDHI, S.V. (Asian Journal of Chemistry, 2010)
Four accurate, sensitive and economical procedures for simultaneous estimation of paracetamol and aceclofenac in tablet dosage form have been developed. The methods employed are simultaneous equation method, first order derivative method, area under curve method and absorbance ratio method for simultaneous estimation of paracetamol and aceclofenac. The first method employs the formation and solving of simultaneous equation using 244 and 273 nm as the two wavelengths for forming equation. The second method employs first order derivative spectroscopy to eliminate spectral interference. The third method employs selection of area under curve in wavelength region of 242-246 and 271-275 nm and solving the equation. The fourth method employed 266 nm as λ1 (isobestic point) and 244 nm as λ2, which is the λmax of paracetamol. The drugs obey Beer's law in the concentration range 10-100 μg/mL for aceclofenac and 10-50 μg/mL for paracetamol. The results of analysis have been validated statistically and by recovery studies.